UJI PENGGUNAAN BAHAN ORGANIK SUMBER BERBEDA TERHADAP PERTUMBUHAN BIBIT NANGKA (Artocarpus heteropyllus Lamk) - Nainggolan, Desmariana; Noer, Abd Hamid; Tjoa, Aiyen (AGROTEKBIS, 2013)
Municipal garbage and seaweed are organic materials which can be soil ameliorant (additive) important to improve soil chemical and physics. Different organic material sources given to the soil will make plants growing on it respond differently except the seeds. This study aim at testing the response given by organic matter from the city garbage and seaweed on marginal soils (with low pH areas, clayey texture and low nutrient content) on the jackfruit seed growth. The research design used is random complete design with 6 treatments and 4 replications. The treatments tested were B0 = (control-without ameliorant), B1 = Soil + (100 mg N, 60 mg P, 100 mg K, 60 mg Mg, Ca 60 mg kg -1 soil)., B2 = Soil + (50 mg N, 30 mg P, 50 mg K, 30 mg Mg, 30 Ca mg kg -1 soil) + organic materials. Sea weed., B3 = Soil + organic materials. Seaweed., B4 = Soil + (50 mg N, 30 mg P, 50 mg K, 30 mg Mg, 30 mg Ca kg -1 soil) + organic materials. Municipal garbage., B5 = Soil + organic materials. municipal garbage. The results showed that the provision of municipal garbage organic and seaweed significantly affect the parameters of leaf width, however, sea weed organic materials has a more significant effect thanÂ municipal garbage.